Deactivation of vascular endothelium by monoclonal anti-tumor necrosis factor alpha antibody in rheumatoid arthritis. - Paleolog, E; Hunt, M; Elliott, M; Feldmann, M; Maini, R; Woody, J (1996)
OBJECTIVE: To assess whether monoclonal antibody to tumor necrosis factor alpha (TNF alpha) reduces endothelial activation in rheumatoid arthritis (RA). METHODS: Levels of serum E-selectin, intercellular adhesion molecule 1 (ICAM-1), and vascular cell adhesion molecule 1 (VCAM-1), and circulating leukocytes (differential counts) were measured in RA patients before and up to 4 weeks after infusion of either placebo or chimeric anti-TNF alpha antibody cA2 (1 or 10 mg/kg). RESULTS: Treatment with anti-TNF alpha decreased serum E-selectin and ICAM-1 levels, with the earliest detectable changes observed on days 1-3 after anti-TNF alpha infusion. No effect on VCAM-1 levels was detected. In parallel, there was a rapid and sustained increase in circulating lymphocytes. The extent of the decrease in serum E-selectin and ICAM-1 levels and the increase in lymphocyte counts was significantly higher (P < or = 0.05) in patients in whom a clinical benefit of anti-TNF alpha was observed ( > or = 20% response, by Paulus criteria, at week 4) compared with that in patients who failed to respond to anti-TNF alpha at this time point. CONCLUSION: We propose that decreased serum levels of adhesion molecules may reflect diminished activation of endothelial cells in the synovial microvasculature, leading to reduced migration of leukocytes into synovial joints, and thus prolonging the therapeutic effect of anti-TNF alpha in RA.